Vocatives and discourse markers in textualinteractive grammar - Penhavel, Eduardo (Linha D'Água, 2012)
In this paper, we discuss the class of Vocatives and the class of Discourse Markers as proposed within Textualinteractive Grammar, and we try to demonstrate that Vocatives can work as Discourse Markers.